Between looking back and moving ahead : an exploration of the role of the body and its movement in a music therapy case study - Bindewald, Mara (2017)
We exist in this world through our bodies. Every single experience is stored in it, it helps us to communicate with others, relate and build meaningful relationships. However, when the connection to our experiences or the control over our body is disrupted by a traumatic experience or disease, we become disconnected from our genuine self and the world around us. Music therapy provides us with a space for integration – of painful or joyful memories, emotions, and our bodies. Especially in Western cultures this physical relationship to music is often neglected, even though music and dance probably developed simultaneously and are still very much the same in some African cultures. When we are moving we are active, can be curious, adventurous, meet our limits, discover discomfort and develop ease. By becoming aware of our bodies and its rhythms, we can work on integrating all those experiences to become a whole, authentic and resilient being. This short-term exploratory music therapy case study therefore is a curious journey of discovery of what can happen when we focus on the relationship between music and body. Some background into how music, emotions and movement are related will help you understand the therapeutic process. The method encompasses important concepts like a definition of this approach to music therapy, the therapeutic and the researcher's stance. Grounded theory and naturalistic inquiry were combined for the analysis of data available in text form, including therapist's notes, thick description and summary of each session, as well as supervision notes. This allowed for more creative discoveries and interpretation. Furthermore the analysis of music and movement interventions from various points of the therapy process enhance and support the text analysis, thus creating a more detailed picture of this case